Optimal survey parameters for the borehole-to-surface controlled source electromagnetic method - Zhang, Zhenghu; Zhou, Nannan (Journal of applied geophysics, 2025)
The Frequency-domain borehole-to-surface controlled source electromagnetic (FD-BSCSEM) method is a geophysical technique used to explore mineral resources and assess engineering geology. However, the optimal selection of operational parameters for borehole-to-surface measurements remains a topic of debate. Through three-dimensional numerical simulations, we investigate the propagation characteristics of current in the BSCSEM method and the impact of various operational parameters on the simulated responses. Using a high resistivity plate-shaped anomaly as a case study, we analyze the effects of offset, source position, and source length on the radial electric field component (Er). Our results show that for anomalies buried at a depth of 500 m, the offset should be limited to within 2000 m to ensure sufficient signal strength and resolution. Charge accumulation is primarily concentrated at the top and bottom surfaces of the anomaly. When the source is sufficiently close to the anomaly, a stronger anomalous response will occur at the surface. When the source length is significantly longer than the thickness of the anomaly, the anomalous signal experiences rapid attenuation; therefore, it is advisable to limit the source length to prevent excessive energy dispersion. Finally, we examined the response of low-resistivity bodies. Compared to high-resistivity anomalies, horizontal currents are more likely to dominate in low-resistivity bodies, leading to differences in parameter selection. •Innovative Approach: We studied BSCSEM survey parameters and found they significantly impact resolution in synthetic model.•3D Numerical Simulation: We analyzed current propagation in anomalies and its impact on responses, offering a basis for optimizing survey parameters.•Key Parameter Analysis: The study shows that for 500 m deep anomalies, offset should be under 2 km to maintain signal strength and resolution.•Electric Field Response Characteristics: The vertical current source are sensitive to high-resistivity bodies, revealing their distribution and relation to anomalies.•Survey Optimization Recommendations: Limiting source length is advised to reduce energy dispersion; source depth and position also affect resolution capability.